Characteristics of Ultrathin Ni Films. Issue 7 (3rd January 2019) - Grilli, Maria Luisa; Vernhes, Richard; Hu, Guohang; Di Sarcina, Ilaria; Dikonimos, Theodoros; Sytchkova, Anna; Martinu, Ludvik; He, Hongbo; Piegari, Angela
Abstract : Conductive and transparent ultra‐thin Nickel films are grown by RF sputtering on fused silica substrates. The characteristics of Ni films (thickness, refractive index, and extinction coefficient) are obtained by fitting multi‐angle spectrophotometric and ellipsometric data. Films thickness inferred by X ray reflection (XRR) measurements is in good accordance with ellipsometric results. XPS analysis reveals that Ni metal phase is present in the film surface together with Ni mixed oxide phases, which explains the high electrical stability of such films. Abstract : Ultra‐thin films play a key‐role in several technological applications. The authors report on the accurate characterization of ultrathin (5–8 nm) Ni films grown by RF sputtering. Thickness and optical constants are inferred by fitting multi‐angle spectrophotometric and ellipsometric data. Thickness values are in very good agreement with XRR results, and higher than the ones estimated by the sputtering rate obtained by profilometry measurements.